Upregulation of Thymidylate Synthase Induces Pemetrexed Resistance in Malignant Pleural Mesothelioma - Sato, Yuzo; Tomita, Masaru; Soga, Tomoyoshi; Ochiai, Atsushi; Makinoshima, Hideki (Frontiers in Pharmacology, 2021)
Malignant pleural mesothelioma (MPM) is an invasive malignancy that develops in the pleural cavity, and antifolates are used as chemotherapeutics for treating. The majority of antifolates, including pemetrexed (PMX), inhibit enzymes involved in purine and pyrimidine synthesis. MPM patients frequently develop drug resistance in clinical practice, however the associated drug-resistance mechanism is not well understood. This study was aimed to elucidate the mechanism underlying resistance to PMX in MPM cell lines. We found that among the differentially expressed genes associated with drug resistance (determined by RNA sequencing), TYMS expression was higher in the established resistant cell lines than in the parental cell lines. Knocking down TYMS expression significantly reduced drug resistance in the resistant cell lines. Conversely, TYMS overexpression significantly increased drug resistance in the parental cells. Metabolomics analysis revealed that the levels of dTMP were higher in the resistant cell lines than in the parental cell lines; however, resistant cells showed no changes in dTTP levels after PMX treatment. We found that the nucleic acid-biosynthetic pathway is important for predicting the efficacy of PMX in MPM cells. The results of chromatin immunoprecipitation-quantitative polymerase chain reaction (ChIP-qPCR) assays suggested that H3K27 acetylation in the 5-UTR of TYMS may promote its expression in drug-resistant cells. Our findings indicate that the intracellular levels of dTMP and dTTP are potential biomarkers for the effective treatment of patients with MPM and suggest the importance of regulatory mechanisms of TYMS expression in the disease.